The virtual-hand illusion: effects of impact and threat on perceived ownership and affective resonance - Ma, Ke; Hommel, Bernhard (Frontiers in Psychology, 2013)
The rubber hand illusion refers to the observation that participants perceive “body ownership” for a rubber hand if it moves, or is stroked in synchrony with the participant’s real (covered) hand. Research indicates that events targeting artificial body parts can trigger affective responses (affective resonance) only with perceived body ownership, while neuroscientific findings suggest affective resonance irrespective of ownership (e.g., when observing other individuals under threat). We hypothesized that this may depend on the severity of the event. We first replicated previous findings that the rubber hand illusion can be extended to virtual hands—the virtual-hand illusion. We then tested whether hand ownership and affective resonance (assessed by galvanic skin conductance) are modulated by the experience of an event that either “impacted” (a ball hitting the hand) or “threatened” (a knife cutting the hand) the virtual hand. Ownership was stronger if the virtual hand moved synchronously with the participant’s own hand, but this effect was independent from whether the hand was impacted or threatened. Affective resonance was mediated by ownership however: In the face of mere impact, participants showed more resonance in the synchronous condition (i.e., with perceived ownership) than in the asynchronous condition. In the face of threat, in turn, affective resonance was independent of synchronicity—participants were emotionally involved even if a threat was targeting a hand that they did not perceive as their own. Our findings suggest that perceived body ownership and affective responses to body-related impact or threat can be dissociated and are thus unlikely to represent the same underlying process. We argue that affective reactions to impact are produced in a top-down fashion if the impacted effector is assumed to be part of one’s own body, whereas threatening events trigger affective responses more directly in a bottom-up fashion—irrespective of body ownership.